1995
DOI: 10.1111/j.1471-6402.1995.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dependency Needs And Perceived Availability And Adequacy Of Relationships In Female Adolescent Suicide Attempters

Abstract: Traditional theories about female adolescent suicide attempters view them as experiencing difficulty in achieving adequate separation‐individuation. However, recent work on female adolescence suggests that achieving greater interdependency within relationships rather than increased independence from them is an important goal for nonclinical nonsuicidal female adolescents. We investigated both dependency needs and the perceived availability and adequacy of relationships in 21 female adolescent attempters and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Bearman & Moody, 2004;Bettridge & Favreau, 1995). Ethnically diverse samples have also been studied (e.g.…”
Section: Present Study and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bearman & Moody, 2004;Bettridge & Favreau, 1995). Ethnically diverse samples have also been studied (e.g.…”
Section: Present Study and Hypothesesmentioning
confidence: 99%
“…Interpersonal relationship problems were also associated with suicide attempts. For example, Bettridge and Favreau (1995) found that adolescent attempters reported less availability of intimate relationships in their lives, significantly less satisfaction in these intimate relationships, and more serious interpersonal conflicts compared with non-attempters. Second, family problems/conflict pose significant suicide risk for children and adolescents.…”
Section: Life Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al (2006) recently reported that problems with current or former intimate partners contributed to nearly 28% of the suicides in the National Violent Death Reporting System for the period 2003–2004, confirming earlier work by Weissman (1974). These statistics reinforce a growing body of research that has found a correlation between actual or intended self‐harm and problems with family or other interpersonal relationships (see Barber, Blackman, Talbot, & Saebel, 2004; Bettridge & Favreau, 1995; Milnes, Owens, & Blenkiron, 2002; Slap, Vorters, Chaudhuri, & Centor, 1989; Wasserman, 1988).…”
mentioning
confidence: 65%
“…According to relational-cultural theory (RCT), numerous aspects of women's health are impacted by the quality and strength of the relationships around them (Miller & Stiver, 1997). RCT asserts that more connected relationships with important others will lead to better quality of life (e.g., Finkelstein, 1996;Frey, Beesley, & Miller, 2006;Perilla, Bakeman, & Norris, 1994;Spencer, 2002), better health (e.g., Amaro, 1995;Bettridge & Favreau, 1995;Lyons, Sayer, Archbold, Hornbrook, & Stewart, 2007), and better mental health (e.g., Hedelin & Jonsson, 2003;Kaplan, 1986;Sanftner et al, 2006;Sanftner, Tantillo, & Seidlitz, 2004;Tantillo & Sanftner, 2003).…”
mentioning
confidence: 99%